Effects of 27-hydroxycholesterol on oligodendrocytes in Alzheimer’s disease: a double-edged sword? - Alanko, Vilma (My University, 2020)
Hypercholesterolemia is an established risk factor for developing Alzheimer’s disease (AD). A proposed link between elevated systemic cholesterol levels and AD is oxysterols: oxidized metabolites of cholesterol, which can cross the blood-brain barrier. It is known that high levels of the oxysterol 27-hydroxycholesterol (27OH) has negative impacts on the brain. Abnormal myelin structure results in the disconnection of neural networks that is an early phenomenon in AD. The effect of high 27OH levels in oligodendrocyte function remains largely unexplored. In this project the aim was to determine whether 27OH affects myelination in the brain. Effects of 27OH in a human oligodendroglioma (HOG) cell line was investigated with immunoblotting and cell viability assay. High concentrations of 27OH cause HOG cell death. In addition, treatment with 27OH may result in alterations in myelin protein expressions. In 3D co-cultures set up with mouse embryonic brain cells, the effects of 27OH on markers of oligodendrocyte differentiation were investigated by immunofluorescence. 27OH treatment elevated differentiation of oligodendrocytes and increased the ratio of oligodendrocytes to other cells. However, myelin abundance in brain sections obtained from wild type and transgenic mice with increased systemic 27OH levels showed no significant differences. Still, a trend to decreased myelin and/or neuronal content in hippocampus was shown in conditions with high 27OH. As a conclusion, 27OH has a beneficial impact on oligodendrocyte maturation in culture, but high concentrations are toxic. Further studies are needed to evaluate the molecular mechanisms behind these dual effects that may represent the complexity of hypercholesterolemia effects on the brain.
Keywords: 27-hydroxycholesterol, myelin, oligodendrocyte, Alzheimer’s disease